1995
DOI: 10.1007/bf00169186
|View full text |Cite
|
Sign up to set email alerts
|

Cultured chick sympathetic neurons: ATP-induced noradrenaline release and its blockade by nicotinic receptor antagonists

Abstract: The ATP-induced increase in tritium outflow from cultured chick sympathetic neurons prelabelled with [3H]-noradrenaline was investigated. Seven days-old dissociated cell cultures of embryonic paravertebral ganglia, loaded with [3H]-noradrenaline (0.05 microM), were superfused in the presence of (+)-oxaprotiline and exposed to ATP, ATP-analogues, or 1,1-dimethyl-4-piperazinium (DMPP) for 2 min. ATP (3 microM-3 mM), 2-methylthio-ATP (3-100 microM), as well as DMPP (10 and 100 microM) induced a significant overfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In cultured chick and rat sympathetic neurons, nucleotide P2‐receptors, when activated, initiate action potential firing and release of previously stored [ 3 H]noradrenaline (Boehm, 1994 ; Allgaier et al, 1995 b ; von Kügelgen et al, 1997). In the mouse neurons, however, ATP did not change the basal outflow of tritium, i.e., did not release [ 3 H]noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured chick and rat sympathetic neurons, nucleotide P2‐receptors, when activated, initiate action potential firing and release of previously stored [ 3 H]noradrenaline (Boehm, 1994 ; Allgaier et al, 1995 b ; von Kügelgen et al, 1997). In the mouse neurons, however, ATP did not change the basal outflow of tritium, i.e., did not release [ 3 H]noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…During early postnatal life, IB 4 -binding DRG neurons (that express P2X3 receptors) switch from nerve growth factor to glial cell-derived neurotrophic factor dependence [222]. P2 receptors modulated NA release from chick sympathetic neurons cultured from 12-dayold embryos [223,224]. This suggested that both a facilitatory P2 receptor and an inhibitory receptor were involved.…”
Section: Peripheral Nervous Systemmentioning
confidence: 99%
“…A study of P2 receptors modulating NA release from chick sympathetic neurons cultured from 12-day-old embryos suggested that two different P2 receptor subtypes were involved: a facilitatory receptor and an inhibitory receptor [147]. In a sister paper, the authors postulated that the ATP receptor involved in NA release acted via a subclass of the nicotinic cholinoceptor [148].…”
Section: Gangliamentioning
confidence: 99%